The Influence of Shopping Experience and Perception of Value on Consumer Satisfaction and Its Impact on Consumer Loyalty in Bojonegoro Fruit Store - Ugid, M. Ugid Subowo; Sujarwo, Sujarwo; Isaska, Riyanti (Sekolah Pascasarjana Universitas Brawijaya, 2024)
This study aims to identify and analyze the influence of shopping experience and perceived value on customer satisfaction at Laskar Buah Store in Bojonegoro, as well as to analyze the direct and indirect effects of shopping experience, perceived value, and customer satisfaction on customer loyalty at Laskar Buah Store in Bojonegoro. This research uses a quantitative descriptive approach with a survey method and data collection technique through questionnaires distributed to customers of the fruit store in Bojonegoro. The sample of this study consists of actively shopping customers at the fruit store, with a total of 100 respondents. The analysis technique used in this research is Structural Equation Modeling (SEM)-PLS. The results of the study indicate that shopping experience has a positive and significant effect on customer satisfaction, shopping experience has a positive and significant effect on customer loyalty, perceived value has a positive and significant effect on customer satisfaction, perceived value has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on loyalty, shopping experience has a positive and significant effect on customer loyalty through the mediation of customer satisfaction, perceived value has a positive and significant effect on customer loyalty through the mediation of customer satisfaction. Keywords: shopping experience, perceived value, customer satisfaction, customer loyalty